2013
DOI: 10.1016/j.chb.2012.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Competence gaps in software personnel: A multi-organizational study

Abstract: a b s t r a c tToday, the innovation and quality of the software industry's products and services depend to a great extent on the knowledge, ability and talent applied by software engineers. At the same time, human aspects are recognized as one of the main problems associated with software development projects. More specifically, inefficiencies usually come from inadequate verification of software engineers' competences. Another issue is the lack of an established career for software engineers, which adds diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 40 publications
1
53
0
1
Order By: Relevance
“…People are key for software development processes [1] and personnel factors are one of the elements that can impact the effectiveness and productivity of software teams [2]. These teams rely on the communication skills and abilities of a software development team, and therefore the productivity of a software organization is affected by the levels of social cohesion among its members [3].…”
Section: Introductionmentioning
confidence: 99%
“…People are key for software development processes [1] and personnel factors are one of the elements that can impact the effectiveness and productivity of software teams [2]. These teams rely on the communication skills and abilities of a software development team, and therefore the productivity of a software organization is affected by the levels of social cohesion among its members [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in DeCom, each competence must be associated with a proficiency level. At DevERP, competences were classified as: undeveloped (1), early development (2), partially developed (3), developed (4), and fully developed (5).…”
Section: Competence Mappingmentioning
confidence: 99%
“…Competence management [1][2][3][4] involves mapping organizational competences needs, identifying competence gaps [5], and filling these gaps through sourcing, training, coaching and other corporate education activities [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…To do this, each person provides, and his/her profile shows, information about their working hours, their current status regarding availability (see right-hand side of Trusty screens in Figure 2), the time people prefer to be contacted, etc. In addition, it has been shown that interruptions have a negative impact on task completion time [14,30], decision-making [31,32], and people's emotional states [33]. Interruptions may also result in prospective memory failure [30,34], which refers to the fact that an individual may have a problem remembering what s/he has to do as regards a planned task (or in this case, the interrupted task).…”
Section: Benevolencementioning
confidence: 99%